Narcotic sparing postoperative analgesic strategies after pancreatoduodenectomy: analysis of practice patterns for 1004 patients. Issue 7 (July 2022) - Jajja, Mohammad R.; Williams, Hannah; Mahmooth, Zayan; Nadeem, Syed O.; Hashmi, Salila S.; Sarmiento, Juan M.
Abstract: Background: Improved post-operative outcomes have been demonstrated in gastrointestinal procedures where a narcotic sparing strategy has been utilized. Data for pancreaticoduodenectomy (PD) patients is limited. This study reviews an institutional database for outcomes based on initial analgesic strategy. Methods: 1004 consecutive patients who underwent PD at Emory University between 2010 and 2017, were included in the analysis. Patients were divided into groups based on primary analgesic strategy employed: epidural alone (EPI), patient controlled opiate analgesia (PCA), dual (dual-PCA/EPI) and other (non-PCA/EPI). Postoperative outcomes for each group were analyzed utilizing univariate and multivariate linear regression. Results: 448 (44.6%) patients were treated with EPI, 300 (29.9%) were given a PCA, 78 (7.8%) had dual-PCA/EPI and 178 (17.7%) had non-PCA/EPI analgesia. On univariate analysis, increased BMI (p = 0.030), PCA use (p < 0.001), venous thromboembolism (VTE) (p < 0.001), post-operative pancreatic fistula (POPF) (p < 0.001) and Ileus/delayed gastric emptying (DGE) (p < 0.001) were all correlated with increased LOS. On multivariate linear regression, VTE (b-coefficient 9.07, p = 0.004) POPF (8.846, p = 0.001), Ileus/DGE (4.464, p = 0.004) and PCA use (1.75, p = 0.003) were associated with significantly increased LOS. Conclusion: A primary narcotic sparing strategy is associated with a significantly reduced LOS and lower rates of Ileus/DGE. Mean opiate usage was significantly lower in the EPI and non-EPI/PCA groups.